Qualitative Analysis: Effective Practices in Inclusive and Special Needs Education in China - Cao Zongqing; Gift Muyunda; Qiangfeng Lab (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2023)
The sphere of inclusive and special needs education has garnered significant attention in contemporary educational discourse. China, as an influential global actor, provides a pertinent case study due to its socio-cultural dynamics and rapid educational reforms. This qualitative analysis seeks to elucidate effective practices prevalent in China's special needs education system and examine their implications for further academic and policy-oriented discussions. A qualitative study method was chosen and in-depth interviews were used to obtain in-depth information. The study sample consisted of 4 teachers,3 students,1 parent and 1 school manager in China using purposive sampling technique. Data analysis was analyzed inductively and successively coded to generate emerging themes. The results of the study shows that special needs children enjoy equal educational access in China, however, there is a lack of systematic and comprehensive support at school level resulting in limited compensatory equity and differential equity. Also, the results of the study show that teachers’ professional ethics and professional level are the keys for implementing relevant policies and ideas and promoting the educational equity of children in regular classes.